TERAPI DIATERMI GELOMBANG MIKRO DAN TRAKSI TRANSLASI PENDERITA HEMIPLEGIA DENGAN GANGGUAN GERAK SENDI BAHU DI RUMAH SAKIT FATMAWATI JAKARTA TAHUN 2015 - Andy Martahan Andreas Hariandja; Jofizal Jannis; Suranto Suranto (Poltekkes Kemenkes Jakarta III, 2017)
Delaying in caring restricted shoulder’s joint motion among haemiplegia patients lead to worsen conditions, which are characterized by the limitations of active and passive movement on the entire movement of the shoulder joint. This study aims to determine the effect of Diathermy Micro Wave therapy and translational traction on the changes in joint motion of shoulder hemiplegia with frozen shoulder. This research uses pre-experiment pre-posttest one group design. The study population was hemiplegic patients with frozen shoulder movement dysfunction. The sample was 15 the patiens in the population those chosed based onpurposive sampling consideration with 30 - 50 years aged. The result of statistical analisys showed that paired t-test for the extent of exorotation of the shoulder joint before and after MWD and traction-translation revealed significant differences with p = 0.014 <α = 0.05; wilcoxone test for abduction before and after administration of MWD and traction-translation made significant different with value of p=0.046 < α=0.05; and wilcoxon test for endorotation shoulder joint area before and after administration of Diathermy Microwaves and traction-translations showed significant differences (p = 0.001 <α = 0.05). The conclusion of this research is the provision of Diathermy Micro Wave intervention and traction-translation can increase the distance of motion abduction, exorotation and endorotation of shoulder joints of Hemiplegia patients with shoulder joint disfunction.